Cardiomyocyte-Restricted High-mobility group box 1 (HMGB1) deletion leads to small heart and inflammation through GR/PGC-1a signaling. (25th November 2020) - Yu, P; Liu, M; Jiang, H
Abstract: : Cardiomyocyte-Restricted High-mobility group box 1 (HMGB1) Deletion Leads to small heart and inflammation Through GR/PGC-1a signaling Background: Cardiac growth and remodeling are key biological process influencing the physiological performance of the heart. Previous study showed critical role of intracellular HMGB1 in vitro. However, the in vivo study using conditional Hmgb1 ablation did not significantly affect the cellular and organic function. Purpose: Previously we have demonstrated the extracellular effect of HMGB1 as a proinflammatory molecule on cardiac remodeling. Here, to elucidate the intracellular effect of HMGB1 on cardiac function in vivo, we perform the study. Methods: Conditional genetic deletion of HMGB1 mouse was constructed using cTnT-Cre Hmgb1fl/fl. And then we detected body weight, and analyzed cardiac function of 12-week old mice using echocardiography. The subcelluar morphology was detected using the transmission electron microscopy (TEM) examination, and the changes of glycolipid metabolism was detected by the positron emission tomography (PET)/computed tomography (CT) imaging and GC-FID/MS analysis in heart tissue. And Then we used RNA-seq to find transcriptomic changes. And co-immunoprecipitation experiments, chromatin immunoprecipiptation (ChIP) were used to validate the binding of HMGB1 and glucocorticoid receptor (GR). The downstream signal changes were detected using western blot analysis. To validate the result, we further constructed the cardiac HMGB1 deficient mouse using Ckmm-Cre Hmgb1fl/fl, and measured body weight and cardiac function. Results: We found HMGB1 deletion by cTnT-Cre in mouse hearts altered GR function, glycolipid metabolism, and eventually led to growth retardation, small heart, and heart failure. The subcelluar morphology didn't show significant change caused by HMGB1 knockout. The heart showed significantly elevation of glycolysis and free fatty acid deposition, and related enzyme changes. Transcriptomic analysis revealed a list of differential expressed genes, which coincide with the glucocorticoid receptor function in neonatal mice, and significant increase inflammatory genes of the adult ones. The cardiac HMGB1 knockout lead to a series changes of PGC-1a, UCP3, and glycerol kinase, which were the cause of metabolic change and further impact the cardiac function. And the Ckmm-Cre Hmgb1fl/fl mouse didn't show significant phenotype, which was consistent with the reported negative result of Cardiomyocyte-specific Hmgb1 deletion via MHC-Cre. Conclusions: Therefore, our results demonstrated that HMGB1 plays an essential role in maintaining normal cardiac growth and function by regulating GR function and glycolipid metabolism. And the strikingly different phenotype from the cardiac-specific HMGB1-deficient mice may be caused by the cross with different Cre mouse. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Natural Science Foundation of China